The relationship between oral health status and the multidimensional health locus of control Among new case diabetes patients located in Maetha district, Lampang Province. - มณีวงศ์ อุดมลักษณ์; นั้นติชัย มุขธิตา (Thai Dental Public Health Journal, 2008)
Locus of control scales have long been demonstrated the relationship to the decision in preventive and curative behavior in human being, psychological factors to physical disease and the response of patients to disease. This cross - sectional study aimed to investigate the relationship between locus of control and oral health status among new case diabetes patients at Maetha district, Lampang province. This study was carried out among 20 males and 31 females with average age 50.73 + 6.85 years old. The Multidimensional Health Locus of Control (MHLC) Scale was used to measure health locus of control with three dimensions; internal, external and chance. Oral health examination was performed by trained oral health personnel using WHO criteria for dental caries status (DMFT), Periodontal status (CPITN) and Debris index. Data was analyzed by using means and medians and non - parametric statistics. The results showed mean score of internal MHLC was 30.18+ 3.56, mean score of external MHLC was 30.86+ 3.42 and mean score of chance MHLC 22.76+ 4.46.Dental caries status was varied from caries free to DMFT = 28, mean of DMFT was 2.29 + 3.02. It was found that subjects with calculus was 54.90%, with periodontal pocket dept more than 4-5 mm. was 41.17%. Debris index range from 1 to 2.67 with mean DI 1.93 + 0.43. It was found that there was significant correlation between the external MHLC dimension with debris index (p value = 0.012). This study suggests that oral health status related to external multidimensional health locus of control.